Usługi finansowe w świetle regulacji podatku od towarów i usług - Olejnik, Marek (Financial Services in the Light of the Act on Goods and Services Tax (Vat), 2005)
The paper presents system principles resulting from the 6th Directive and their implementation into the Polish Act on Goods and Services Tax. It presents the scope of financial operations not subject to the exemption from VAT, issues of tax base and place, and of an influence of occasional financial transaction on the settlement of input tax. The paper shows discrepancies resulting from the national legislation and the most important decisions of the European Court of Justice on financial transactions concerning VAT.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1073, s. 116-124